The Relationship Between Internet Use and Mental Health Among Older Adults in China: The Mediating Role of Physical Exercise - Zhang S (Dove Medical Press, 2021)
Sheng Zhang,1,2 Yujie Zhang2 1China Institute for Urban Governance, Shanghai Jiao Tong University, Shanghai, 200030, People’s Republic of China; 2School of International and Public Affairs, Shanghai Jiao Tong University, Shanghai, 200030, People’s Republic of ChinaCorrespondence: Yujie ZhangSchool of International and Public Affairs, Shanghai Jiao Tong University, 1954 Huashan Road, Xuhui District, Shanghai, 200030, People’s Republic of ChinaTel +86-186-9696-0193Email zhangyujie@sjtu.edu.cnObjective: Affected by internet applications, mental health among older adults has become an important public health issue in China. This study aimed to use cross-sectional data to explore how internet use affects mental health among older adults in China, along with the moderating role of physical exercise in the above relationship.Methods: This study employed data from the Chinese General Social Survey (CGSS) conducted in 2017. In addition, OLS regression was adopted to explore the impacts of internet use on the mental health of older adults in China.Results: Results from the cross-sectional data model showed that internet use had a statistically significant and positive correlation with the mental health of older adults. The regression result of the full sample showed that the regression coefficient of the influence of internet use on the mental health of the elderly was 0.114, which was significant at the 1% level. Furthermore, this study used mediating analysis to explore the possible underlying mechanism by which internet use influenced mental health status through physical exercise. Physical exercise played a mediating role in the relationship between internet use and mental health; the ratio of the indirect effect to total effect mediated was 0.272. It is important to note that the effect size of the indirect effect through physical exercise was quite large.Conclusion: Our findings suggested that internet use was significantly associated with better mental health status for older Chinese residents, mediated by higher physical exercise frequency, which was consistent with China’s recent efforts to promote health governance with the “Internet Plus Exercise” campaign. Consequently, the government must encourage the development of more internet applications suitable for the elderly to increase their exercise frequency and ultimately improve their mental health. These results also provided insights for clinical solutions.Keywords: internet use, mental health, physical exercise, older adults, health governance